Memory in a time of prose: studies in epistemology, Hebrew scribalism, and the biblical past - Pioske, Daniel D. (Oxford University Press USA - OSO, 2018)
Memory in a Time of Prose investigates a deceptively straightforward question: what did the biblical scribes know about a past that consumed so many of their writings? This book compares biblical references to an early Iron Age world (ca. 1175-830 BCE) with a wide range of archaeological and historical evidence from the era in which these stories are set in order to reveal how the past was preserved, transformed, or forgotten within biblical storytelling.